Resting Heart Rate Responses After Three Months of Intensive Exercise - Diaz, Diaz Irfansyah; Sumartiningsih, Sri; Rex John Guilabo Bawang, Rex John Guilabo Bawang (Journal of Sport Science and Fitness, 2025)
Introduction: Resting heart rate (RHR) is a key indicator of cardiovascular adaptation in athletes, reflecting physiological responses to intensive training. While decreased RHR typically signifies improved cardiovascular efficiency, variability in adaptation based on factors like training duration, intensity, and individual characteristics remains understudied in young athletes. Objectives: This study aims to analyze the resting heart rate (RHR) response in young athletes after participating in an intensive 15-week training program. Method: The study uses a quasi-experimental design with a pre-test and post-test approach. The sample consists of 15 male and female athletes who are members of the National Sports Design Program (DBON). Physiological variables were measured using digital devices: a heart rate monitor for RHR, a pulse oximeter for oxygen saturation (SpO₂), and a digital scale and height measurer to calculate body mass index (BMI). Measurements were taken before and after the training program. Data were analyzed descriptively (Mean ± SD), and statistical tests were performed using SPSS software. Normality was tested using the Shapiro-Wilk test, and homogeneity of variance was tested using Levene’s test. Paired t-tests were used to determine differences between pre- and post-values, while Pearson correlation tests were used to examine relationships between variables, with significance set at p < 0.05. Result: The results showed no significant changes in RHR, SpO₂, or BMI, and no significant relationship was found between RHR and SpO₂. Conclusion: This study recommends long-term physiological monitoring and the use of additional parameters to assess exercise adaptation more comprehensively.